ANALISIS SOSIOLOGI EKONOMI DALAM PENGELOLAAN DAN PENYALURAN DANA SOSIAL STUDI KOMPARATIF ANTARA DANA ZAKAT INFAK SADAQAH (ZIS) DAN DANA KOLEKTE - Sarwo Eddi Wibowo (LPPM University 17 Agustus 1945 Samarinda, 2020)
This study aims to analyze the management and distribution of social funds viewed from the perspective management funds of Zakat, Infaq, Sadaqah and Dana Kolekte to conducted by Muslims and Catholics communities in people needed. The method used in this study is a qualitative descriptive approach. Data collection techniques using in depth interviews, observation and literature review. The results of this study indicate that Zakat, Infaq, Sadaqah and Dana Kolekte have very large role for community development, especially people of each religion. The aspects of economic sociology focus on community empowerment and poverty alleviation through philanthropic funds such as Zakat, Infaq, Sadaqah and Dana Kolekte that provide significant influence and benefits for people in needed